Effect of Uric Acid-Lowering Agents on Patients With Heart Failure: A Systematic Review and Meta-Analysis of Randomised Controlled Trials - Xu, Hongxuan; Liu, Yunqing; Meng, Lingbing; Wang, Li; Liu, Deping (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background Elevated serum uric acid (SUA) level is considered an independent predictor of all-cause mortality and the combined endpoint of death or readmission in cardiovascular disease patients. However, the causal relationship between uric acid lowering therapies (ULTs) and heart failure is still controversial. Design Meta-analyses were performed to systematically compile available evidence to determine the overall effect of UlTs on heart failure patients. Method This systematic review was conducted in accordance with the PRISMA statement guidelines. Databases were searched to identify randomized controlled trials related to the influence of an ULTs intervention in people with heart failure. Data extracted from the included studies were subjected to a meta-analysis to compare the effects of ULTs to a control. Results Pooled analysis of Left Ventricular Ejection Fraction (LEVF) showed an insignificant result towards the ULTs group (MD, 1.63% 95%CI -1.61 to 4.88 p=.32; 3 studies). Pooled analysis of Six-Minute Walk Test(6MWT) showed an insignificant result towards the ULTs group (MD 4.59 95%CI -12.683 to 22.00 p=.61; 4 studies). Pooled analysis of BNP/NT-pro-BNP showed a nearly statistically significant result towards the ULTs group (SMD -0.30 95%CI -0.64 to 0.04 p=.08; 5 studies). Pooled analysis of all-cause mortality and cardiovascular death between ULTs (all XOIs) and placebo did not show a significant difference (RR 1.26 95% CI 0.74 to 2.15, P=.39). Conclusion ULTs did not improve LVEF, BNP/NT-pro-BNP, 6MWT, all-cause mortality, and CV death in heart failure patients. UA may just be a risk marker of heart failure.